Bloom drivers of the potentially harmful dinoflagellate Prorocentrum minimum (Pavillard) Schiller in a south eastern temperate Australian estuary. (31st December 2018) - Ajani, Penelope A.; Larsson, Michaela E.; Woodcock, Stephen; Rubio, Ana; Farrell, Hazel; Brett, Steve; Murray, Shauna A.
Abstract: Harmful algal blooms are an increasing concern in the estuarine reaches of the Hawkesbury-Nepean River, one of the largest coastal rivers systems in south eastern Australia. In the austral spring of 2016, an unprecedented bloom of the harmful mixotrophic dinoflagellate Prorocentrum minimum occurred in Berowra Creek (maximum cell abundance 1.9E+06 cells L −1, 89% of the total phytoplankton community), a major tributary of this river system. In response to this bloom, our study utilises an estuary-wide, thirteen-year time series of phytoplankton abundance and environmental data to examine the spatial and temporal patterns of this harmful alga and its potential bloom drivers in this system. P. minimum cell densities and environmental parameters varied over large spatial scales, with sites located in the main channel of the estuary significantly differing from those in the more urbanized tributary of Berowra Creek. Generalised additive modelling outputs suggested that blooms of P. minimum are complex, but generally corresponded to a spatial gradient of eutrophication and salinity, whereby P. minimum growth and concomitant high chlorophyll-a concentrations were enhanced at sites that were generally less saline and more eutrophic than others. Furthermore, temporal patterns suggested that blooms occurred abruptly and lasted up to three weeks, most often during the austral autumn to spring. While significant correlations were observed between rainfall and nutrients at all other sites, suggesting a pathway for nutrient availability, the association between rainfall and nutrient delivery was generally not observed in Berowra Creek (a 15-m deep site) suggesting that a continual supply of nutrients, coupled with unique bathymetry and water residence time at this site, are the most likely contributing factors to phytoplankton growth. This study presents the most comprehensive examination of P. minimum in any southern hemisphere estuary to date and highlights the importance of continued monitoring of HABs and the important role that anthropogenic inputs have in driving blooms of P. minimum in this oyster-growing river/estuary system.